Effect of plastic slatted flooring on growth and welfare of stall-fed kids - RAMACHANDRAN, N; SINGH, S P; KUMAR, ARVIND; POUROUCHOTTAMANE, R; RANJAN, RAVI; RAI, B; INDORE, NAVNATH; GOEL, A K (The Indian Journal of Animal Sciences, 2020)
Male kids (36) at 6 months age, 12 each of Jamunapari, Jakhrana, Barbari breed were equally divided and allotted randomly in plastic and soil floor and reared up to 12 of age through April to September months, fed ad lib. roughage, green fodder and concentrate to meet nutrient requirements for optimum growth. Body weight was recorded fortnightly, physiological responses were recorded twice and blood sampling at 60th and 120th day of trial. The weight gain and ADG on plastic floor was similar as compared to soil floor. Kids were equally comfortable on both floors except RR; however, increased RR on plastic floor did not affect the weight gain in kids. Plasma AST and ALT enzymes, total protein, albumin, total cholesterol, triglycerides level differed non-significantly in kids reared on both plastic and soil floor indicating the suitability of plastic floor in goat shelters in semi-arid conditions.